A study on the prevalence of dental caries among the school-going children in Tamil Nadu - Parasuraman, Gomathy; Gowtham Krishna, Y.; Kaviya, M.; Jain, Nischal A.; Rajendran, Prashanth; Dutta, Ruma (International Journal Of Community Medicine And Public Health, 2017)
Background: Dental caries is an important social problem in India and is predominantly a disease of childhood. The prevalence and incidence of dental caries is influenced by various socio–demographic factors like age, sex, ethnic groups, dietary patterns and oral hygiene habits. The objective of the study were to estimate the prevalence of dental caries among the school going children aged between 5–10 years and to determine the risk factors associated with dental caries. Methods: A population based cross–sectional study was conducted among the primary school going children in Thirumazhisai from February 2016 to July 2016. Simple random sampling technique was employed and 357 children were identified for the study. Descriptive statistics was calculated for background variables and association between the risk factors and evidence of dental caries was analyzed by tests of proportions and chi square test was used as a statistical test of significance. Results: The overall prevalence of dental caries was found to be 63.9%. Higher prevalence of dental caries was found among the girls (54%), among the lower socioeconomic class (41.7%), among those who consumed mixed diet (74.8%), among those who consumed junk foods (62.6%) at least once every day and among those who consumed dairy products (58.9%) at least once every day. Dental caries was found to be low in prevalence among those who consumed fruits several times a week (6.1%), among those who brushed their teeth twice/more than twice a day (20.2%) and among those who washed their mouth after each meal (38.7%). Conclusions: Lack of awareness, improper dietary habits and poor oral hygienic practices are seemingly the contributing factors for the development of dental caries. Dental caries is a preventable disease which can be alleviated by creating community awareness through health education activities.